2021
DOI: 10.1097/oi9.0000000000000158
|View full text |Cite
|
Sign up to set email alerts
|

Rates and timing of short-term complications following operative treatment of tibial shaft fractures

Abstract: Introduction: Tibial shaft fractures are a relatively common injury in orthopaedic surgery, with management options including intramedullary nail (IMN) fixation or open reduction internal fixation (ORIF) with plate osteosynthesis. Using a large national database, we sought to compare the prevalence and timing of short-term complications following either IMN or ORIF for tibial shaft fractures.Methods: The American College of Surgeons National Surgical Quality Improvement Program was used to identify patients un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
0
7
0
2
Order By: Relevance
“… 3 Another study of 4,963 tibial shaft fractures showed an overall infection rate of 0.02% within 30 days of ORIF/IMN but different rates of infection between open and closed fractures were not reported. 19 In that same study though, a higher American Society of Anesthesiologists score, congestive heart failure, and hypertension were associated with acute infection. 19 In 480 patients with tibial shaft fractures, another study did not identify any patient comorbidities as risk factors for acute infection.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“… 3 Another study of 4,963 tibial shaft fractures showed an overall infection rate of 0.02% within 30 days of ORIF/IMN but different rates of infection between open and closed fractures were not reported. 19 In that same study though, a higher American Society of Anesthesiologists score, congestive heart failure, and hypertension were associated with acute infection. 19 In 480 patients with tibial shaft fractures, another study did not identify any patient comorbidities as risk factors for acute infection.…”
Section: Discussionmentioning
confidence: 87%
“… 19 In that same study though, a higher American Society of Anesthesiologists score, congestive heart failure, and hypertension were associated with acute infection. 19 In 480 patients with tibial shaft fractures, another study did not identify any patient comorbidities as risk factors for acute infection. 13 By contrast, our study specifically investigated open tibial shaft fractures and accounted for patient comorbidities granularly as compared with amalgamated scores such as CCI or American Society of Anesthesiologists.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Similarly, during this period, patients are also likely progressing to union, which increases the PROMIS PF score differences as patients return The literature cites high rates of risk factors and complications after tibial shaft fractures including roughly 15%-39% are open fractures, infection rate of 2%-30%, and nonunion rate ranging 3%-7%, and reoperation rates ranging from 12% to 44%. 1,[3][4][5][6][7][8][9][10][11]39 This study had similar rates of open fractures and complications with 104 (27.2%) open fractures, 25 (6.5%) infections, 42 (11%) nonunions, and 104 (27.2%) secondary surgeries. This lends confidence to that the overall cohort is representative of operatively treated tibial shaft fractures.…”
Section: Discussionmentioning
confidence: 92%
“…(5)(6)(7)(8) Malalignment is a common complication of IMN for TSFs, which has been reported to account for 19-41% of cases, (9,10) due to the lack of endosteal t at the fracture site and the means of assessing rotation around the shaft axis intra-operatively. (11) Malalignment of MIPO for TSFs has a similar incidence because the technical complexity of achieving anatomical alignment made closed reduction a demanding surgical technique. (7) The radiation exposure of the operating staff and the patient are another serious de ciency associated with MIPO and IMN which is caused by closed reduction.…”
Section: Introductionmentioning
confidence: 99%